Analisis Keputusan Pendanaan Untuk Menilai Profitabilitas Pada PT Bank Jatim - Rachmawati, Rani; Sutrismi, Sri (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This study aims to determine the management of funding sources at PT Bank Jatim Tbk. whether it has shown a more efficient prospect, to determine the impact of funding sources on profitability at PT Bank Jatim Tbk. The data in this study were obtained from published annual reports which were samples in the study of historical data on financial statements for the last 5 (five) years, from 2019 to 2023. The type of research used in the study is quantitative descriptive. The data processed are DER (Debt to Equity Ratio), DAR (Debt to Assets Ratio), LDE (Long term Debt to Equity Ratio), ROA (Return On Assets), ROE (Return On Equity) The calculation technique used in the study is to calculate the percentage of the ratio. While the data analysis technique used is descriptive quantitative analysis. Based on the results of calculations and data collection, the results show that funding source decisions reduce profitability from the DER (Debt to Equity Ratio) indicator, DAR (Debt to Assets Ratio), LDE (Long term Debt to Equity Ratio), ROA (Return On Assets), ROE (Return On Equity).